Distribution of dye-decolorizing peroxidase (DyP) genes among bacteria based on the NCBI database - Mustafa Irfan; Suharjono; Ardyati Tri; Jatmiko Yoga Dwi (BIO Web of Conferences)
Synthetic textile dyes, such as anthraquinones, are durable and persistent to microbial degradation, making them toxic to the environment. Certain bacteria have been reported to possess dye-decolorizing peroxidase (DyP) enzymes, which show potential for degrading anthraquinones. The isolation of local bacteria with DyP genes is crucial to addressing this issue in Indonesia. Therefore, to increase the likelihood of obtaining these potential bacteria, it is essential to gather information on the distribution of DyP genes across different bacterial species reported to date. This study was conducted in silico to investigate the distribution of DyP-coding genes in various bacterial species using the NCBI database. The results revealed that DyP enzymes are mostly found in members of the phylum Actinobacteria compared to those in the phyla Firmicutes and Proteobacteria. These findings serve as a foundational reference for guiding methods in the isolation of dye-degrading bacteria possessing DyP enzymes.